Motorola's Droid 2 : the product manager's dilemma - Sawhney, Mohanbir S. (SAGE knowledge. Cases., 2016)
After it introduced the extremely successful Droid smartphone into the market in 2009, Motorola quickly moved to develop the next-generation Droid 2 before the next wave of smartphones (including the rumored iPhone 4) flooded the market. The development process was moving smoothly for the company when Verizon, its biggest partner, dropped a bombshell: It wasn't happy with the mechanical camera button on the Droid 2 and wanted it to be changed to a software button like the iPhone's. This case explains how Motorola dealt with this awkward dilemma.